2016
DOI: 10.1182/blood-2015-10-679191
|View full text |Cite
|
Sign up to set email alerts
|

TNFRSF14 aberrations in follicular lymphoma increase clinically significant allogeneic T-cell responses

Abstract: Key Points• TNFRSF14 gene aberrations, common in FL, increase the ability of lymphoma cells to stimulate allogeneic T-cell responses.• TNFRSF14 lesions were associated with increased acute GVHD supporting stratified transplantation approaches in the allogeneic setting.Donor T-cell immune responses can eradicate lymphomas after allogeneic hematopoietic stem cell transplantation (AHSCT), but can also damage healthy tissues resulting in harmful graftversus-host disease (GVHD). Next-generation sequencing has recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Blockade of LIGHT-HVEM signaling has also been shown to increase the rate of survival of solid allografts, including pancreatic islets and cardiac transplants (141,142). Recently, lymphoma B cells from patients with mutations in the HVEM gene (TNFRSF14) were found to have increased alloantigen-presenting capacity in comparison to controls, corresponding to higher levels of GVHD in patients undergoing allogeneic hematopoietic stem cell transplantation (143). In murine experimental autoimmune uveitis (EAU), a model of human autoimmune conditions with ocular manifestations such as Behçet disease and sarcoidosis, HVEM was shown to increase disease severity by inducing pathogenic Th1-and Th17-type T cell responses (144).…”
Section: Hvem Signaling Impacts a Variety Of Human Diseases Offeringmentioning
confidence: 99%
“…Blockade of LIGHT-HVEM signaling has also been shown to increase the rate of survival of solid allografts, including pancreatic islets and cardiac transplants (141,142). Recently, lymphoma B cells from patients with mutations in the HVEM gene (TNFRSF14) were found to have increased alloantigen-presenting capacity in comparison to controls, corresponding to higher levels of GVHD in patients undergoing allogeneic hematopoietic stem cell transplantation (143). In murine experimental autoimmune uveitis (EAU), a model of human autoimmune conditions with ocular manifestations such as Behçet disease and sarcoidosis, HVEM was shown to increase disease severity by inducing pathogenic Th1-and Th17-type T cell responses (144).…”
Section: Hvem Signaling Impacts a Variety Of Human Diseases Offeringmentioning
confidence: 99%
“…In a previous study, reduced TNFRSF14 expression was suggested to contribute to the pathobiology of classical Hodgkin lymphoma (8). Another previous study indicated that TNFRSF14 deficiency promotes development of follicular lymphoma in vivo and establishes a favorable immune environment (9). Cheung et al (10) reported that somatic TNFRSF14 mutations are associated with worse prognosis of follicular lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…BTLA and TNFRSF14 crosstalk regulates inhibition and costimulation of several key players of the immune system: BTLA functions as an inhibitory receptor in T lymphocytes 16 while the ligand TNFRSF14 produces proinflammatory signals via activation of NF-kappaB 17 and it is expressed by antigen presenting cells 18 . Interestingly, TNFRSF14 aberrations in FL increase clinically significant allogeneic T-cell responses 19 and in non-small cell lung cancer TNFRSF14 may contribute to the immune escape 20 …”
Section: Introductionmentioning
confidence: 99%